Digital twin inception in the Era of industrial metaverse - Mourtzis, Dimitris (Frontiers in Manufacturing Technology, 2023)
Digital Twins, as a technological pillar of Industry 4.0, correspond to the virtual representation and bi-fold a real-time communication of a digital counterpart of a process or a physical object. As the industrial and manufacturing landscape is shifting towards Industry 5.0, huge investments focusing on enhancing interactions between Operators and Cyber-Physical Systems (CPS) occur. Yet, Metaverse strengthens these interactions as it enables human immersion into a virtual world. Furthermore, it examines the very promising relationships between the CPS, through the digital twins of these CPS. Therefore, this short review presents the concept of the Digital Twin inception in Industrial Metaverse. Additionally, a service-oriented digital twin architecture with Metaverse-enabled platforms for added value creation and interactions with CPS towards achieving Industry 5.0 challenges and beyond is proposed.